2022
DOI: 10.1186/s13756-022-01126-7
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study of barriers to antimicrobial stewardship in Indonesian hospitals: governance, competing interests, cost, and structural vulnerability

Abstract: Background Antimicrobial resistance (AMR) is one of the leading global public health threats of the 21st Century. Antimicrobial stewardship (AMS) programmes have been shown to improve antibiotic use and clinical outcomes in high-income settings, but context-specific evidence is lacking on the value and effectiveness of current AMS programmes in low-resource settings. This study sought to explore context-specific underlying barriers to AMS implementation in Indonesian hospitals with a focus on g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 38 publications
(26 reference statements)
0
5
0
Order By: Relevance
“…Of the 22 studies that documented barriers to ASP adoption, 50% (11/22) reported a shortage of human resources [ 27 37 ]. Eleven studies each identified the absence of leadership and minimal governmental support [ 27 , 28 , 35 42 ], and a lack of reliable laboratory infrastructure and microbiology laboratory support as challenges to effective ASP implementation [ 28 , 29 , 31 , 35 , 36 , 38 , 40 , 42 45 ]. Other identified barriers included inadequate orientation and training on ASP including rational antimicrobial use [ 27 , 30 , 36 , 41 , 44 , 46 ], prescribers’ negative attitudes to changes in antibiotic practices [ 27 , 30 , 33 , 35 , 37 , 43 , 47 ], and a lack of dedicated ASP funds [ 28 , 32 , 33 , 36 , 37 , 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…Of the 22 studies that documented barriers to ASP adoption, 50% (11/22) reported a shortage of human resources [ 27 37 ]. Eleven studies each identified the absence of leadership and minimal governmental support [ 27 , 28 , 35 42 ], and a lack of reliable laboratory infrastructure and microbiology laboratory support as challenges to effective ASP implementation [ 28 , 29 , 31 , 35 , 36 , 38 , 40 , 42 45 ]. Other identified barriers included inadequate orientation and training on ASP including rational antimicrobial use [ 27 , 30 , 36 , 41 , 44 , 46 ], prescribers’ negative attitudes to changes in antibiotic practices [ 27 , 30 , 33 , 35 , 37 , 43 , 47 ], and a lack of dedicated ASP funds [ 28 , 32 , 33 , 36 , 37 , 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…Several barriers to implementing effective antimicrobial stewardship (AMS) strategies have been identified in the literature. For example, Limato et al, 18 found that healthcare professionals (including microbiologists, pharmacists, physicians, surgeons, and hospital managers) described how ineffective resources, competing priorities and insufficient medical facilities prevented AMS strategies from being effective. Other research highlighted that although awareness of AMS in wound care has been found to be high, the measurement of the impact of AMS programs or strategies is low, 19 therefore increasing education around how AMS activities can be measured is an important aspect of reducing the impact of AMR in healthcare.…”
Section: Ams and Wound Carementioning
confidence: 99%
“…48 This problem is further reinforced by the British Society for Antimicrobial Chemotherapy (BSAC) and European Wound Management Association (EWMA) position paper 25 stating that AMS is fundamental to promoting the appropriate use of antimicrobials, including antibiotics, and in reducing AMR. 25,33 Given that wound management accounts for 16.4% of all systemic antibiotic prescriptions 18 varying levels of clinical knowledge have been shown to further contribute to the inconsistent use of antimicrobials. 48 Improving professional education, particularly around furthering clinician understanding of the need for more sustainable use of antibiotics is, therefore, a core focus of the UK Department of Health's 2019-2024 five-year antimicrobial stewardship strategy, 49 Antimicrobial Resistance Strategy 2020 and Beyond.…”
Section: Current Research On Amr and Skin Integritymentioning
confidence: 99%
“… 4 , 5 The Indonesian government has undertaken measures to regulate the use of antibiotics by reinforcing its national antibiotic stewardship program and promoting their cautious consumption. 6 , 7 However, despite these efforts, improper antibiotic use remains widespread in Indonesia. 6 …”
Section: Introductionmentioning
confidence: 99%
“…4,5 The Indonesian government has undertaken measures to regulate the use of antibiotics by reinforcing its national antibiotic stewardship program and promoting their cautious consumption. 6,7 However, despite these efforts, improper antibiotic use remains widespread in Indonesia. 6 The insufficient knowledge regarding the appropriate use of antibiotics is commonly recognized as a significant factor that contributes to their misuse and subsequently contributes to the emergence of drug-resistant microorganisms.…”
Section: Introductionmentioning
confidence: 99%